2014
DOI: 10.1097/mnm.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for N2 metastasis in patients with non-small-cell lung cancer

Abstract: SUV(max) and tumor cell grade are independent risk factors for N(2) metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The T_SUVmax threshold of 6.05 is not directly comparable to the one reported in other studies: we did not seek an optimal threshold but a threshold minimizing the number of occult lymph nodes. However, it is interesting to note that this threshold remains in the same range as those previously reported between 4 ( 13 ) and 7.5 ( 12 ). The study by Vansteenkiste et al ( 17 ), although not directly concerning occult LNI, reported a better 2-year survival when the primary tumor had SUV lesser than 7 and tumor size lower than 3 cm.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The T_SUVmax threshold of 6.05 is not directly comparable to the one reported in other studies: we did not seek an optimal threshold but a threshold minimizing the number of occult lymph nodes. However, it is interesting to note that this threshold remains in the same range as those previously reported between 4 ( 13 ) and 7.5 ( 12 ). The study by Vansteenkiste et al ( 17 ), although not directly concerning occult LNI, reported a better 2-year survival when the primary tumor had SUV lesser than 7 and tumor size lower than 3 cm.…”
Section: Discussionsupporting
confidence: 84%
“…For unresectable tumors, it would allow better planning of radiotherapy and possible adjuvant treatments. Overall, some 18F-FDG PET/CT predictors of occult LNI have already been described: primary tumor localization as central and right superior lobe tumors are associated with a greater risk of occult N2 node (6); primary tumor size: the negative predictive value of 18F-FDG PET/CT was higher for tumors of less than 3 cm in diameter (9)(10)(11); primary tumor 18F-FDG uptake (11)(12)(13). The objective of this study is to build and validate a model to identify patients without LNI more accurately than the simple visual interpretation of 18F-FDG PET/CT.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many evidences support the relationship between a high FDG uptake in the primary tumor and the risk of lymphatic or distant metastatic spread, 12,22 the risk of occult mediastinal metastasis in case of low SUV value is less convincing or even contradicted by recent works. 23 Several meta-analyses on eUS-FNa alone, eBUS-TB-Na alone, and combined eUS+eBUS reported a pooled sensitivity of 83% to 94% for mediastinal staging of lung cancer. [24][25][26][27][28][29][30] Only one randomized controlled trial 31 has been performed, comparing the two staging strategies proposed in the eSTS 2007 guidelines (either mediastinos-tions with the descriptor R or L added to denote laterality (r, right; L, left).…”
Section: Staging Of Lung Cancermentioning
confidence: 99%